Open-source hardware for medical devices. Issue 2 (14th March 2016) - Niezen, Gerrit; Eslambolchilar, Parisa; Thimbleby, Harold
Abstract : Open-source hardware is hardware whose design is made publicly available so anyone can study, modify, distribute, make and sell the design or the hardware based on that design. Some open-source hardware projects can potentially be used as active medical devices. The open-source approach offers a unique combination of advantages, including reducing costs and faster innovation. This article compares 10 of open-source healthcare projects in terms of how easy it is to obtain the required components and build the device.